Evidence of congenital heart disease in the offspring of parents with atrioventricular defects. Issue 2 (February 1983) - Emanuel, R; Somerville, J; Inns, A; Withers, R
Abstract : Fifty-two of the 56 offspring from 90 patients with proven atrioventricular defects were examined. There were five with congenital heart disease. The defects were concordant in three and discordant in two. The mother was the affected propositus in all cases. In this relatively small sample the incidence of congenital heart disease in the offspring of parents with atrioventricular defects was 9.6%, or 14.3% if only the female propositi were considered. This is a much higher figure than that reported for the simple forms of isolated congenital heart disease.